Validity and reliability of the Arabic version of the EuroQOL (EQ-5D). A study from Saudi Arabia - Bekairy, Abdulkareem; Bustami, Rami; Almotairi, Mohammed; Jarab, Anan; Katheri, Abdulmalik; Aldebasi, Tariq; Aburuz, Salaheddin (International Journal of Health Sciences, 2018)
Objectives: This study is aimed at evaluating the validity and reliability of the Arabic version of the EQ-5D in Saudi Arabia. Methods: The study was done utilizing a convenience sample of Arabic-speaking adult patients or visitors at the outpatient clinic at King Abdulaziz Medical City (KAMC) in Riyadh during October – December 2015. Participants were interviewed using translated-into-Arabic versions of the EQ-5D and the Short Form Health Survey (SF-36). Known-group construct validity of the EQ-5D and visual analogue scale (EQ-VAS) was assessed through testing a number of hypotheses comparing responses to EQ-5D dimensions or EQ-VAS to SF-36 scores by dimention and external variables. Test-retest reliability was also assessed. Results: Eighty subjects were included. Mean ± SD age was 33.0 ± 11.6 years, with 51% females. Responses to EQ-5D dimensions revealed that the proportion of respondents reporting problems ranged from 6% for problems with self-care to 48% for pain/discomfort. All of the five hypotheses linking EQ-5D responses to external variables were satisfied. Test-retest reliability was evaluated using Cohen's κ, which ranged from 0.53-1.00. Conclusion: Validity and reliability of the Arabic EQ-5D was established for evaluating HRQOL in Saudi Arabia. Further studies are warranted to evaluate the validity and reliability of this standard tool in other Arabic-speaking countires with varying cultures.